Marketplace lending of small‐ and medium‐sized enterprises - Cumming, Douglas; Hornuf, Lars (Strategic Entrepreneurship Journal, 2022)
Abstract Research Summary When evaluating Internet‐based loan project of small and medium size enterprises (SME), lenders can rely on easy‐to‐understand risk ratings or more sophisticated financial information. We investigate lenders decisions and its effect on loan funding success on the marketplace‐lending platform Zencap. The data set has been provided by the platform Zencap and includes 414 SME marketplace loans and 2,196 lenders. The data examined provide strong support for the importance of simple platform ratings in influencing investor behavior, while the effect of more detailed financial information is less pronounced, controlling for relevant variables. Higher interest rates appear more profitable to investors without any serious concern about non‐repayment. Managerial Summary Platform managers and potential borrowers are interested in how to encourage lenders to pledge their money on marketplace‐lending platforms. We investigate the influence of easy‐to‐understand risk ratings and more sophisticated financial information on investment decisions and their effect on loan funding success on the marketplace‐lending platform Zencap. We investigate 414 SME marketplace loans and 2,196 lenders. We find that for marketplace lending on Zencap the effect of more detailed financial information is less pronounced than easy‐to‐understand risk ratings. Platforms base risk ratings on information other than the entrepreneurs' financial information.